Examining the Relationship Between Psychological Abnormalities and Emotional Interactions with Emotional Divorce with the Mediating Role of Religious Beliefs in Couples with Marital Conflicts - Faghih Tabaghdehi, Alireza; Sheikhi Ghahderijani, Nasibeh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the relationship between psychological abnormalities and emotional interactions with emotional divorce, with the mediating role of religious beliefs in couples experiencing marital conflicts.Methods: The research method was descriptive and correlational. The statistical population of this study included all couples visiting counseling centers in the city of Neka (Neda-e-Zendegi Counseling Center, Phoenix Counseling Center, Amin Counseling Center, Imam Ali Social Work Counseling Center, and Mental Health Counseling Center) during the first six months of 2022, totaling 686 individuals (343 couples). Using the Krejcie and Morgan table, the sample size was calculated to be 246 individuals, and through a convenience sampling method, those who were interested in participating in the study were selected as the sample. They responded to questionnaires on psychological abnormalities by Najarian and Davoodi (2001), emotional interactions of couples by Brok and Bretman (1995), emotional divorce by Gottman (1995), and religious beliefs by Najafi (2006). Data analysis was performed using the Kolmogorov-Smirnov test, Pearson correlation test, and structural equation modeling with SPSS and AMOS software.Findings: The findings showed that psychological abnormalities had a positive effect on emotional divorce and a negative effect on religious beliefs. Additionally, emotional interactions had a negative effect on emotional divorce and a positive effect on religious beliefs. Furthermore, religious beliefs had a negative effect on emotional divorce in couples. On the other hand, the results indicated that religious beliefs played a mediating role in the relationship between psychological abnormalities, emotional interactions, and emotional divorce in couples.Conclusion: This study highlights the indirect effect of psychological disorders and emotional interactions on emotional divorce, with religious beliefs playing a mediating role among couples experiencing marital conflicts. The findings suggest that strengthening religious beliefs may help reduce emotional divorce, emphasizing the need for interventions that promote emotional well-being and healthy marital dynamics.